The role of cryptic developmental plasticity in the origination of new phenotypes - Lofeu, Leandro (2020)
Developmental modifications inducing a complex phenotype that until then did not exist in a given population or lineage (a new phenotype), is a central theme within evolutionary developmental biology (Evo-Devo). However, it remains unclear how much developmental processes facilitate, bias or even constrain diversification patterns among lineages. Especially considering that, given their multifactorial and multilayer nature, developmental mechanisms involved in the first induction of a phenotype are not necessarily the same ones later involved in its evolutionary fixation, maintenance and modification. This fact is clearly illustrated by evolutionary events driven by genetic accommodation of traits initially induced by environmental signals. Developmental plasticity has emerged in the theoretical literature as an important promoter of phenotypic diversification during evolution, however its frequency and relevance in such processes remains elusive. The present work consists in an investigation of the potential of developmental plasticity in inducing new phenotypes under particular environmental conditions, using the neotropical fish Megaleporinus macrocephalus (Anostomidae) as a model. In the first part of this work, experimental manipulations are performed combining different factors to create different developmental environments, followed by multivariate analyzes of phenotypes based on morphospace approach. The results demonstrate that cryptic developmental plasticity can quickly give rise to new head morphotypes, previously nonexistent in the ancestral population (fishery). Furthermore, phylogenetic multivariate analyzes show that plastic morphotypes also represent previously unoccupied regions in the Anostomidae morphospace, clearly representing an increase of phenotypic diversity in the group. In the second part, are investigated 3 internal processes underlying the expression of plastic morphotypes: i) patterns of head modularity by using correlation/covariance matrices, ii) mechanical stress on the condrocranium using Finite Element Analysis (FEA) and, iii) the analysis of the differential expression of candidate genes by qPCR. Taken together, these 3 results suggest that starting from a conserved number of mechanisms and, under particular environmental contingencies, developmental plastic responses can promote broad diversification in morphospace by accommodating new and viable phenotypes.